The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2020.581347
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of Clinical Target Volumes for Post-Modified Radical Mastectomy Radiotherapy Using Convolutional Neural Networks

Abstract: BackgroundThis study aims to construct and validate a model based on convolutional neural networks (CNNs), which can fulfil the automatic segmentation of clinical target volumes (CTVs) of breast cancer for radiotherapy.MethodsIn this work, computed tomography (CT) scans of 110 patients who underwent modified radical mastectomies were collected. The CTV contours were confirmed by two experienced oncologists. A novel CNN was constructed to automatically delineate the CTV. Quantitative evaluation metrics were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Both the generator and discriminator of the cGAN observe the input CBCT image. In this study, we implement a full convolutional neural network (CNN) architecture 24 as the generator. In this CNN architecture, a U-Net backbone architecture is utilized; it consists of an encoding path and a decoding path.…”
Section: Methodsmentioning
confidence: 99%
“…Both the generator and discriminator of the cGAN observe the input CBCT image. In this study, we implement a full convolutional neural network (CNN) architecture 24 as the generator. In this CNN architecture, a U-Net backbone architecture is utilized; it consists of an encoding path and a decoding path.…”
Section: Methodsmentioning
confidence: 99%
“…The HD95 measure the 95 th quantile of the distribution of surface distances instead of the maximum. This metric is more robust towards outlier segmented pixels than the HD and thus is often used to evaluate automatic algorithms [38,30].…”
Section: Assessment Aimmentioning
confidence: 99%
“…In our previous work, we have demonstrated that CNN architecture could facilitate the delineation of CTV for radical mastectomy radiotherapy. 30 In this piece of work, we focused on both CTV and OARs for breast conservative radiotherapy. We also made some modifications in CNN architecture.…”
Section: Discussionmentioning
confidence: 99%